The Effect of Shopping Lifestyle, Hedonic Shopping Motivation, and Sales Promotion on Impulsive Buying Among Gen Z Consumers on E-Commerce - Husnul Khatimah; Jamalludin Harahab; Vina Amanda; Devita Indriyani (International Journal of Applied Business and International Management, 2024)
In the current digital age, characterized by rapid technological advancement, a multitude of platforms have emerged that offer a plethora of features One such platform is TikTok. However, over time, it has been utilized as a cost-effective and time-efficient means of promotion. Subsequently, TikTok launched TikTok Shop, enabling users to directly purchase products from the application. This study sets out to examine the phenomenon of impulsive buying on the TikTok Shop platform, focusing in particular on the case of Generation Z (Gen Z) consumers in Bekasi who tend to make impulse purchases through TikTok Shop. The sample was selected using the method of purposive sampling, with 100 respondents. The results of the t-test suggest that shopping lifestyle and sales promotion exert a positive and significant influence on impulsive buying. However, hedonic shopping motivation is found to be a non-significant predictor of this behavior. The lack of significance in the influence of hedonic shopping motivation may be attributed to the fact that consumers are primarily influenced by other practical factors. Consequently, further in-depth research is required by other researchers to explore impulsive buying which is influenced by various factors, including economic factors and the services offered.